Risk profiles of the preterm behavioral phenotype in children aged 3 to 18 years - Fitzallen, Grace C.; Griffin, Alison; Taylor, H. Gerry; Kirby, James N.; Liley, Helen G.; Bora, Samudragupta (Frontiers in Pediatrics, 2023)
Objective: Characterize the Preterm Behavioral Phenotype in children born preterm by identifying distinct profiles based on patterns of symptomatology or severity of the risk for attention-deficit/hyperactivity disorder, autism spectrum disorder, and anxiety, and determine their associations with child sex, gestational age, and chronological age.Methods: Sample comprised 2,406 children born preterm aged 3-18 years with primary caregiver behavioral ratings on the standardized Strengths and Weaknesses of ADHD Symptoms and Normal Behavior Scale, Social Responsiveness Scale, and Preschool Anxiety Scale or Screen for Child Anxiety and Related Emotional Disorders.Results: Statistical fit indices of latent profile analysis supported a 3-profile model as optimal. Using this model, 75% of children born preterm were identified as having low expression, 20% moderate expression, and 5% high expression profiles of the Preterm Behavioral Phenotype described as co-occurring symptomatology of attention-deficit/hyperactivity disorder, autism spectrum disorder, and anxiety. Male children were more likely than females to be categorized in the moderate expression (Relative Risk Ratio [RRR]=1.29, 95% CI=1.05-1.59), and high expression profiles (RRR=1.77, 95% CI=1.17-2.66). Children born extremely preterm were more likely than those born moderate/late preterm to be categorized in the moderate (RRR=1.68, 95% CI=1.30-2.19) and high expression profiles (RRR=2.06, 95% CI=1.31-3.25). Finally, those in the school-age (RRR=1.68, 95% CI=1.32-2.14; RRR=1.95, 95% CI=1.21-3.13), early adolescence (RRR=1.85, 95% CI=1.38-2.48; RRR=2.61, 95% CI= 1.53-4.44) and late adolescence (RRR=2.09, 95% CI=1.38-3.19; RRR=2.28, 95% CI=1.02-5.08) periods were more likely than those in the preschool period to be categorized in the moderate and high expression profiles, respectively.A quarter of children born preterm were at elevated risk for manifesting symptomatology across all three domains of the Preterm Behavioral Phenotype. Findings emphasize accounting for symptom co-occurrence of this phenotype in neurodevelopmental follow-up and psychosocial interventions to optimize child outcomes.